Factors Affecting Labor Productivity in the Coconut Oil Industry in Kekeran Hamlet, Batu Layar Village, West Lombok Regency - Wawan Turmuzi Baedowi; Helmy Fuadi; Ahmad Zaenal Wafik (Indonesian Development Economics and Localities, 2026)
This study investigates the factors influencing labor productivity in the coconut oil industry in Kekeran Hamlet, Batu Layar Village, West Lombok Regency. Utilizing a quantitative approach, the research focuses on four independent variables—wages, age, work experience, and gender—while labor productivity serves as the dependent variable. Data were collected through surveys, interviews, and documentation involving 52 randomly selected respondents from a population of 108 workers. The analysis employed Confirmatory Factor Analysis (CFA) and Principal Component Analysis (PCA) to assess the significance and contribution of each factor. The results show that wages are the most dominant factor affecting productivity, followed by gender differences. The study highlights the importance of adequate compensation and gender-sensitive approaches to enhance productivity in local resource-based industries. Recommendations for future research include the use of Common Factor Analysis for deeper exploration and comparison.